Mechanisms of regulation of oocyte meiotic maturation - Conti, Marco (Henry Stewart Talks, 2019)
Morphology of oocyte meiotic maturation, Intra-follicular paracrine regulations control oocyte maturation and ovulation, Oocyte maturation & ovulation signalling cascade, The cAMP signalling module, The superfamily of phosphodiesterases (specifically PDE3A), The cGMP signalling pathway, NPR2/NPPC signalling module, EGF like growth factors, LH-induced meiotic maturation scheme